Financial sector developments and economic performance : the Jamaica experience - Barnes, Ainsworth (Caribbean Centre for Monetary Studies [St. Augustine]TT, 1996)
Examines the impact of financial sector developments on the performance of the productive sectors of the Jamaican economy over the last decade.